It had to be you : the Gossip Girl prequel - Von Ziegesar, Cecily (New York : Little, Brown, 2007)
Reveals the effects on a trio of bright, attractive, fifteen-year-old friends--Serena van der Woodsen, Blair Waldorf, and Nate Archibald--when Serena considers leaving their seemingly-perfect life of luxury in New York's Upper East Side for boarding school.
"Poppy."
Keywords: High schools -- Fiction; Interpersonal relations -- Fiction; Wealth -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction